Gastrointestinal bleeding of undetermined origin - Müller Gras, Augusto J (Cirugía del Uruguay, 1999)
The authors present a basicalfy diagnostic and therapeutical approach as regards bleeding of the _ g _ astrointestinal tract not associated to any gwdmg symptoms or signs, whose topography and/or etiology is sti/1 undetermined in spite of total conventional endoscopica/ studies or because of /ack of them due to technical or patient reasons. The authors inc/ude upper and lower bleeding, moderate and severe, ongoing ar detained.